2021
DOI: 10.1039/d1cy00868d
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature vanadium-free catalyst for selective catalytic reduction of NO with NH3 and theoretical study of La2O3 over CeO2/TiO2

Abstract: High-temperature SCR catalyst of La2O3-CeO2/TiO2 was prepared by an impregnation method. The effect of CeO2 and La2O3 content on the NO conversion was studied and the experiment result showed that...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…[8][9][10] However, plenty of shortcomings such as inevitable biological toxicity, narrow active window, inferior low-temperature SCR activity, strong SO 2 oxidation ability, and poor resistance to alkali, alkaline earth, and heavy metal poisoning still exist and restrain the further application of vanadium-based catalysts. [11][12][13][14] Thus, it is still quite urgent to develop nonvanadium catalysts that can express better SCR activity and poisoning resistance that broaden the application potential. Among various kinds of metal oxide-based catalysts, Fe 2 O 3based catalysts possess environment-friendly characteristics, outstanding thermal stability, great N 2 selectivity, eminent mid-to-high SCR activity, and remarkable tolerance to SO 2 at high temperatures, which is a potential candidate that can be applied for the NH 3 -SCR reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] However, plenty of shortcomings such as inevitable biological toxicity, narrow active window, inferior low-temperature SCR activity, strong SO 2 oxidation ability, and poor resistance to alkali, alkaline earth, and heavy metal poisoning still exist and restrain the further application of vanadium-based catalysts. [11][12][13][14] Thus, it is still quite urgent to develop nonvanadium catalysts that can express better SCR activity and poisoning resistance that broaden the application potential. Among various kinds of metal oxide-based catalysts, Fe 2 O 3based catalysts possess environment-friendly characteristics, outstanding thermal stability, great N 2 selectivity, eminent mid-to-high SCR activity, and remarkable tolerance to SO 2 at high temperatures, which is a potential candidate that can be applied for the NH 3 -SCR reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The catalyst prepared by the ball milling method using Ce(OH) 4 and La(OH) 3 instead of Ce 2 (CO 3 ) 3 and La 2 (CO 3 ) 3 as raw materials was denoted as BH-10Ce–2La/TiO 2 . The catalysts prepared by the impregnation method 7 and co-precipitation method 11 according to the literature were labeled as IN-10Ce–2La/TiO 2 and CN-10Ce–2La/TiO 2 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…3(c), the lower binding energy (529.5-530 eV) of O1s is attributed to lattice oxygen, denoted as O b ; the higher binding energy (531.4-531.8 eV) is attributed to surface unsaturated oxygen, denoted as O a ; and the highest peak (532-532.8 eV) corresponds to adsorbed water, denoted as O g . 7,10 Because O a has a higher mobility than the lattice oxygen O b , O a can lead to form more surface oxygen vacancies and subsequently be more highly active in oxidation reactions. As can be seen from Table 3, the O a concentration (76.92%) and O a /(O a + O b ) ratio (47.62%) of BC-10Ce-2La/TiO 2 are the highest among all catalysts, which is favorable for the oxidation of NO to NO 2 in the "fast SCR" mechanism.…”
Section: Characterization Of Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Doping or addition of other elements is a common way to improve the water and sulfur tolerance as well as the catalytic activity. Fan et al reported that a Mn-doped LaMnO 3 catalyst exhibited a long-term NO conversion of 95% along with high N 2 selectivity not affected by SO 2 and H 2 O. Wang et al found that La 3+ played a role in reducing the NH 3 and NO adsorption energies of CeO 2 /TiO 2 catalysts in the NH 3 –SCR reaction. Chen et al prepared manganese oxide (MnO x ) doped with several metals (Zr, Ni, and Co) by an impregnation method using biochar (BC) as the carrier.…”
Section: Introductionmentioning
confidence: 99%